Patent ductus arteriosus and pulmonary hypertension in a fifteen-year-old boy with congenital rubella syndrome and cerebral palsy: a case report - Putri, Jeanaya Hedya Alfara; Haris, Ivana Angelica; Nahdah, Jaudah; Putri, Jenniefer Clarissa; Hamdy, Irza Hasanal; Pikir, Rizqi Rokhmadhoni; Adam, Olivia Mahardani; Adiwinoto, Ronald Pratama (Medical Faculty of Brawijaya University, Indonesia, 2025)
Introduction: Congenital Rubella Syndrome (CRS) is characterized by congenital cataracts, congenital heart disease (CHD), hearing loss, and developmental delay. It is caused by maternal rubella infection during pregnancy, transmitted transplacentally or via respiratory droplets. CRS carries a high risk of morbidity and mortality, with approximately 10–20% of affected infants dying within the first year of life. This case report describes a 15-year-old boy with CRS who developed pulmonary hypertension (PH) due to a persistent patent ductus arteriosus (PDA). Case Description: A 15-year-old boy presented with progressive abdominal distension over one week. Initially suspected of having nephritic syndrome, further evaluation revealed bilateral congenital cataracts, non-cyanotic CHD in the form of PDA, sensorineural hearing loss, and developmental delay, fulfilling criteria for CRS. The patient also exhibited delayed motor milestones (walking at age seven) and limb rigidity suggestive of cerebral palsy (CP). Echocardiography confirmed PDA (0.4 cm) with severe tricuspid and aortic regurgitation, and chest X-ray demonstrated cardiomegaly with PH. The PDA was successfully closed using an Amplatzer Duct Occluder (ADO) via catheterization. Conclusion: This case underscores the importance of early diagnosis and intervention in CRS patients with PDA to prevent irreversible pulmonary vascular disease. Despite a very late PDA closure at age 15, the patient achieved hemodynamic improvement and maintained functional capacity, highlighting that catheter-based closure remains feasible and beneficial even in adolescence. Multidisciplinary care, including timely cardiac intervention and neurodevelopmental support, can improve quality of life in CRS survivors.